2020
DOI: 10.1371/journal.pcbi.1008156
|View full text |Cite
|
Sign up to set email alerts
|

Modeling microbial metabolic trade-offs in a chemostat

Abstract: Microbes face intense competition in the natural world, and so need to wisely allocate their resources to multiple functions, in particular to metabolism. Understanding competition among metabolic strategies that are subject to trade-offs is therefore crucial for deeper insight into the competition, cooperation, and community assembly of microorganisms. In this work, we evaluate competing metabolic strategies within an ecological context by considering not only how the environment influences cell growth, but a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 60 publications
(86 reference statements)
0
33
0
Order By: Relevance
“…For CA, a CS emerges without interspecies communication, simply because, at the species level, the growth rates of species 1 and 2 are limited by the uptake rates of A e and B e , respectively. This is a known result from chemostat modelling [18]. Thus, at their steady state concentrations, the species reach a self stabilizing equilibrium, where neither species can grow faster than D = 1.…”
Section: Coexistence Microbial Consortiummentioning
confidence: 65%
See 1 more Smart Citation
“…For CA, a CS emerges without interspecies communication, simply because, at the species level, the growth rates of species 1 and 2 are limited by the uptake rates of A e and B e , respectively. This is a known result from chemostat modelling [18]. Thus, at their steady state concentrations, the species reach a self stabilizing equilibrium, where neither species can grow faster than D = 1.…”
Section: Coexistence Microbial Consortiummentioning
confidence: 65%
“…Different combinations of microbial and substrate concentrations may give rise to multiple valid steady states. Models that take the extracellular environment into account are frequent in the chemostat literature [18,19]. However, the illustrative small scale models conventionally used in chemostat modelling do not possess intracellular metabolic networks with degrees of freedom in the fluxes, and are thus not concerned with decision making in the same way as FBA-models that use internal degrees of freedom to optimize some objective.…”
Section: Chemostat Vs Batch Environmentmentioning
confidence: 99%
“…predation) [28], or rapid evolution [29]. Recent work has suggested that both thermodynamic inhibition [6] and metabolic trade-offs [7] can allow more survivors than substrates, though it has since been suggested that metabolic trade-offs only support increased diversity for a very narrow and specific parameter range [30]. The proteomic trade-off that our model includes represents a more detailed version of the metabolic trade-off previous work has considered, where instead of a fixed "enzyme budget" the fraction of the proteome that is available to split between reactions inversely proportional to the size of the ribosome fraction.…”
Section: Discussionmentioning
confidence: 99%
“…When we do allow for evolutionary changes, ecological coexistence could become destabilized. When the coexistence is stable even under evolutionary changes, I will refer to it as evolutionary coexistence (termed 'evolutionarily stable coexistence' by Li et al 13 ), which leads to an evolutionarily singular coalition (ESC) defined in adaptive dynamics 14 . In this case a coalition is a collection of phenotypes, that can occur through evolutionary branching, but also through e.g.…”
Section: Evolutionary Optimum Evolutionarily Stable Strategies (Ess) and Evolutionarily Singular Coalitions (Esc)mentioning
confidence: 99%